The Impact of E-Procurement Systems in the Biomedical Industry - A. Seetharaman; Nitin Patwa; Simon Lai Koek Wai; Ahammed Shamir (STIE Malangkucecwara, 2020)
The evolution of the Internet has revolutionised the sourcing and procurement processes in organisations in every industry. The focus of this paper is to analyse the perception of business users on the factors which impact the usage of eprocurement systems in the biomedical industry. There are four factors identified in this research: i.e. control and compliance, cost savings, process automation, and improvements and transparency. The benefit of achieving process automation is the first biggest factor, followed by the need for control and compliance, and transparency, being the second and third factors respectively. The fourth factor, cost savings, is ignored because the users perceived that cost savings will not be realised in the short term, and the returns from the investment could be a couple of years after the eprocurement system has been fully operational. The research also concludes that the ability to perform business analytics and to strengthen the supply chain are the most important factors in measuring the success in the adoption of e-procurement systems